2015
DOI: 10.1111/adj.12233
|View full text |Cite
|
Sign up to set email alerts
|

Loading and composite restoration assessment of various non‐carious cervical lesions morphologies – 3D finite element analysis

Abstract: Background: The present study analysed the effects of different occlusal loading on premolars displaying various non-carious cervical lesions morphologies, restored (or not) with composites, by 3D finite element analysis. Methods: A three-dimensional digital model of a maxillary premolar was generated using CAD software. Three noncarious cervical lesions morphological types were simulated: wedged-shaped, saucer and mixed. All virtual models underwent three loading types (100 N): vertical, buccal and palatal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 37 publications
1
28
0
23
Order By: Relevance
“…This is probably due to elimination of the ‘sharp’, wedge‐shaped apex after restoration with a resin composite (with elastic modulus similar to dentine), resulting in even distribution of occlusal loads. Our previous studies have also indicated that NCCLs with sharp, acute angles display greater stress concentration at the apex than those with rounded apices, and that the resin composite restorations result in similar distribution of stress in different types of NCCLs similar to sound teeth …”
Section: Discussionmentioning
confidence: 85%
“…This is probably due to elimination of the ‘sharp’, wedge‐shaped apex after restoration with a resin composite (with elastic modulus similar to dentine), resulting in even distribution of occlusal loads. Our previous studies have also indicated that NCCLs with sharp, acute angles display greater stress concentration at the apex than those with rounded apices, and that the resin composite restorations result in similar distribution of stress in different types of NCCLs similar to sound teeth …”
Section: Discussionmentioning
confidence: 85%
“…Among all factors involved in this process, the role of the stress has been much discussed in the literature (LEE;EAKLE, 1984;MICHAEL et al, 2009;GRIPPO et al, 2012;FRAGOSO et al, 2013;SOARES et al, 2015;ZEOLA et al, 2015). The term "abfraction" has been used for decades to describe the loss of tooth structure by overcoming bonds between hydroxyapatite crystals due to the stress concentration, distant from the area which the force was applied (LEE;EAKLE, 1984;GRIPPO et al, 2004;MICHAEL et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The term "abfraction" has been used for decades to describe the loss of tooth structure by overcoming bonds between hydroxyapatite crystals due to the stress concentration, distant from the area which the force was applied (LEE;EAKLE, 1984;GRIPPO et al, 2004;MICHAEL et al, 2009). Actually, occlusal interferences, parafunctional habits and bruxism change the magnitude, direction, frequency, duration and localization of the occlusal contacts, which result in different biomechanical behavior in these non-physiological situations (OMMERBORN et al, 2007;BRANDINI, PEDRINI, et al, 2012;BRANDINI, TREVISAN, et al, 2012;SOARES et al, 2015;ZEOLA et al, 2015). Then, these excessive loads generate dental tissues flexion which reaches the ultimate structure resistance and makes the structure more susceptible to other NCCLs etiological factors (LEE E EAKLE, 1984;MICHAEL et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Com a diminuição da prevalência da doença cárie, em resposta às bem sucedidas estratégias de promoção da saúde oral, mais atenção vem sendo dada às outras condições orais, como as lesões cervicais não-cariosas (LCNC) (Senna et al, 2012). Essas lesões são definidas como a perda da estrutura dental na junção esmalte-cemento, sem relação com atividade bacteriana (Mair, 1992;Holland et al, 1997;Soares et al, 2015) As LCNC possuem uma variedade de formas e são bastante comuns na prática clínica (Levitch et al, 1994). Possivelmente, o formato das lesões possui relação com sua etiologia Eakle, 1984) e a severidade e a prevalência aparentam ser maiores em indivíduos com idade mais avançada (Levitch et al, 1994;Schaffner, 2000).…”
Section: Lista De Figurasunclassified
“…A erosão/biocorrosão é definida como a dissolução de tecido dental, camada por camada, através da ação de ácidos, tanto extrínsecos quanto intrínsecos, como o ácido gástrico ou os provenientes da dieta. Já a abfração é a perda tecidual patológica dos tecidos dentais devido às cargas biomecânicas da mastigação, que resultam em flexão do dente e fadiga do esmalte e dentina com consequente fratura (Grippo, 1991;Soares et al, 2014;Soares et al, 2015). Lee e Eakle (1984) propuseram que o estresse tensional causado durante cargas oclusais possuem importante papel no desenvolvimento de lesões cervicais.…”
Section: Hipersensibilidade Dentinária Cervical E Fatores Associadosunclassified